Attitudes of Swiss Health Care Providers Toward Childhood Immunizations. Issue 6 (June 2017) - Schuler, Marianne; Schaedelin, Sabine; Aebi, Christoph; Berger, Christoph; Crisinel, Pierre-Alex; Diana, Alessandro; Niederer-Loher, Anita; Siegrist, Claire-Anne; Vaudaux, Bernard; Heininger, Ulrich
Abstract : Background: INFOVAC is a network providing information about immunization issues to health professionals. The aim of this study was to assess the attitude of INFOVAC subscribers toward the current Swiss immunization schedule, potential modifications, and current and hypothetical immunization practices regarding their own children. Methods: In March 2015, a Web-based survey was sent to 4260 physicians and pharmacists subscribed to INFOVAC. Participation was anonymous and voluntary. The following information was obtained: (1) current immunization status of own children; (2) which immunizations would currently be accepted for a hypothetical own child and (3) attitudes toward potential modifications of the Swiss immunization schedule. Descriptive methods and multivariate models to correct for covariables were used for data analysis. Results: Nine hundred and fifty-five valid questionnaires were received: 886/3704 (23.9%) from physicians and 69/556 (12.4%) from pharmacists. Current (>95%) and hypothetical (>99%) immunization rates were high for diphtheria, tetanus, pertussis, poliomyelitis and measles-mumps-rubella. Most pediatricians (61%) would support more vaccines for their children than currently recommended by the Swiss immunization advisory committee, whereas about 50% of other physicians and pharmacists would decline at least one of the recommended immunizations, most frequently varicella, pneumococcal or meningococcal C conjugate vaccines. Strong general support was expressed for the expansion of human papillomavirus immunization to males, acceleration of the measles-mumps-rubella schedule and a 2 + 1 instead of 3 + 1 diphtheria-tetanus-pertussis, acellular-inactivated poliomyelitis vaccine (DTPa-IPV)/ Haemophilus influenzae type b ± hepatitis B virus (HBV) schedule. Conclusions: Survey participants generally demonstrated a positive attitude toward immunization, with pediatricians being the most progressive subgroup with the largest percentage of participants (63.1%) neither declining nor postponing any recommended immunization. Abstract : Supplemental Digital Content is available in the text.